Drivers of Sinoatrial Node Automaticity in Zebrafish: Comparison With Mechanisms of Mammalian Pacemaker Function - Stoyek, Matthew R.; MacDonald, Eilidh A.; Mantifel, Melissa; Baillie, Jonathan S.; Selig, Bailey M.; Croll, Roger P.; Smith, Frank M.; Quinn, T. Alexander (Frontiers in Physiology, 2022)
Cardiac excitation originates in the sinoatrial node (SAN), due to the automaticity of this distinct region of the heart. SAN automaticity is the result of a gradual depolarisation of the membrane potential in diastole, driven by a coupled system of transarcolemmal ion currents and intracellular Ca2+ cycling. The frequency of SAN excitation determines heart rate and is under the control of extra- and intracardiac (extrinsic and intrinsic) factors, including neural inputs and responses to tissue stretch. While the structure, function, and control of the SAN have been extensively studied in mammals, and some critical aspects have been shown to be similar in zebrafish, the specific drivers of zebrafish SAN automaticity and the response of its excitation to vagal nerve stimulation and mechanical preload remain incompletely understood. As the zebrafish represents an important alternative experimental model for the study of cardiac (patho-)physiology, we sought to determine its drivers of SAN automaticity and response to nerve stimulation and diastolic stretch. Using a pharmacological approach mirroring classic mammalian experiments, along with electrical stimulation of intact cardiac vagal nerves and the application of mechanical preload to the SAN in isolated zebrafish atria, we demonstrate that the principal components of the coupled membrane- Ca2+ pacemaker system that drives automaticity in mammals are also active in the zebrafish SAN and that the effects of extra- and intracardiac control of heart rate seen in mammals are also present in the zebrafish. Overall, these results, combined with previously published work, support the utility of the zebrafish as a novel experimental model for studies of SAN (patho-)physiological function.